2011
DOI: 10.1007/s00441-011-1151-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of heat shock proteins 60, 70, 90, and A2 in rabbit testis

Abstract: Currently, no reports exist concerning the expression patterns and developmental changes of heat shock proteins (HSPs) in the reproductive system of the male rabbit. In the present study, the testes of rabbits were collected at post-natal months 1, 2, 3, 4, 5, and 40. HSP60, HSC70, HSP90, and HSPA2 were detected by both Western blot and immunohistochemical methods. The expression levels of HSP60 and HSC70 showed no apparent change during the developmental progress. HSP90 increased at the second month; prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 37 publications
5
32
0
Order By: Relevance
“…It is widely distributed in the spermatogonia, Sertoli cells, and round spermatids in the rabbit testis (Wu et al 2011). In contrast, the expression of stress-inducible HSP70 is hardly detectable under normal growth conditions, but greatly elevated after exposure to environmental or physiological stresses (Brown et al 1993;Chen et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is widely distributed in the spermatogonia, Sertoli cells, and round spermatids in the rabbit testis (Wu et al 2011). In contrast, the expression of stress-inducible HSP70 is hardly detectable under normal growth conditions, but greatly elevated after exposure to environmental or physiological stresses (Brown et al 1993;Chen et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Biggiogera et al (1996) showed that HSP90 is present in the cytoplasm of all male germ cell types during mouse spermatogenesis. HSP90 has been detected mainly in spermatogonia and elongated spermatids in rabbit testis (Wu et al 2011). A porcine study showed that HSP90 transcripts are constitutively expressed in porcine tissues including kidney, liver, brain, and heart, and their levels are markedly enhanced after a 30-min hyperthermia treatment at 43°C (Huang et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular chaperone heat shock proteins (Hsps) engage in the assembly and disassembly of other proteins and assist in their folding (Wu et al 2011). Hsps localize to different cellular compartments; their expression is also different in these compartments.…”
Section: Introductionmentioning
confidence: 99%